International Security in a World of Fragile States Islamic States and Islamist Organizations - Ibrahimi, S. Yaqub (University of Michigan Press, 2022)
Following the 9/11 attacks on New York and Washington, DC, there has been an increasing interest among scholars, students, and the interested public to study and learn about the Islamist-oriented terrorist organizations called Jihadi Salafi Groups (JSGs). Considering that these organizations emerged in highly fragile states, S. Yaqub Ibrahimi asks: how and why is state fragility linked to the emergence of JSGs? Ibrahimi bases his study on three events: the establishment of al-Qaeda in Afghanistan in 1998, the rise of Islamic State in the post-Saddam Hussein Iraq, and the failed al-Qaeda effort to establish a base in Saudi Arabia in 2003. These case studies contain major aspects and features of the rise of JSGs and, together, explain the contribution of state fragility to the process of the formation and expansion of these terrorist organizations. International Security in a World of Fragile States stands out as a pivotal work on the interconnection between the root causes of JSGs and state fragility conditions and their amalgamated role in the formation and evolution of these organizations. It contributes to IR and international security debates by developing a comprehensive but readily understandable narrative of the rise of JSGs in Islamic countries, and examining them in an analytical framework in which their root causes are categorized on individual, group, and international levels.